Model predictive control based stacked asymmetric multilevel inverter driver - Hassan, Dr. Raaed F.; Yasin, Dr. Naseer M. (International Journal of Engineering and Technology, 2018)
A new structure of a multi-level inverter has been constructed and simulated in this paper to feed a three-phase load. The proposed inverter is a five-level three-phase asymmetric cascade topology. Each phase leg is configured by stacking three-level flying capacitor converter (FCC) and three-level diode clamped converter (DCC). A model predictive current control (MPCC) is employed for generating gating signals that minimize the predefined cost function. These gating signals is applied to the switches of the inverter in the future sample interval. Results from Simulation show the effectiveness of the suggested inverter in achieving the desired results with a significant reduction in the number of flying capacitors and clamping diodes.